E-learning development tendencies in higher education and future directions - Uhomoibhi, James (2011)
Teachers and students in higher education are coming to realize that to become competent practitioners there is need to take advantage of up-to-date digital technologies and learning practices. Learning process requires measurement and evaluation of students behaviour. In the case of e-learning, evidence is sought for improvements resulting from the use of online tools and processes desired to achieve a given set of learning outcomes. In this 21st century, knowledge is fast becoming a powerful engine in life. The visions, innovations, and inventions are the building blocks of developing knowledgeable and sustainable society. E-learning has facilitated the use of a plethora of internet and web-based applications as the method of communication with a distributed audience. Therefore, institutions of higher learning are constantly venturing into new and innovative methods and are radically changing the educational practice making it competitive. This paper examines how emerging technologies and e-learning are being used in education to create a major shift in the educational service paradigm that promises major advantages over the traditional distance learning and face-to-face systems. The authors present developments in distance education and e-learning whilst clarifying the similarities and differences between them. We identify factors affecting development of e-learning systems and examine the implementation of some systems in pervasive distributed computing environments. For everyone everywhere, the present developments in e-learning spells more access for learners, cautionary expansion for universities, and accelerated learning and influences for the future. The future directions is such that the higher educational system of the future and especially in Europe must aim to meet human development needs with elearning playing some major parts through promotion of access and widening participation in knowledge and skills acquisition. In order to support learning in evolving dynamic environments, several factors must be taken into consideration. These range from policies, strategies, the current education environments and business needs as well as the specific discipline being studied. Since the advent of e-learning and its eventual implementation in higher education, the world of learning for both the advanced nations and emerging economies have witnessed an upsurge in the number and types of students who are now engaged in pursuit of studies at institutions of higher learning. This paper reports on issues relating to expectations of the university of the future and the future of universities.